Urban Areas as a Subject for Polish Tourism Geography - Liszewski , Stanisław (Turyzm/Tourism, 2008)
This article is a review and its aim is to present research into urban areas by Polish tourism geographers. In presenting the main research trends. the author has discussed work on the following issues: the tourism assets and function of urban areas, urban tourism space, the market analysis of a tourism urban area. the leisure time of urban inhabitants, and the study of urban tourism landscapes. In the conclusion the author presents the most important issues, in his opinion, awaiting study by Polish tourism geographers.